Multiple Roles of Actin in Exo- and Endocytosis - Wu, Ling-Gang; Chan, Chung Yu (Frontiers in Synaptic Neuroscience, 2022)
Cytoskeletal filamentous actin (F-actin) has long been considered a molecule that may regulate exo- and endocytosis. However, its exact roles remained elusive. Recent studies shed new light on many crucial roles of F-actin in regulating exo- and endocytosis. Here, this progress is reviewed from studies of secretory cells, particularly neurons and endocrine cells. These studies reveal that F-actin is involved in mediating all kinetically distinguishable forms of endocytosis, including ultrafast, fast, slow, bulk, and overshoot endocytosis, likely via membrane pit formation. F-actin promotes vesicle replenishment to the readily releasable pool most likely via active zone clearance, which may sustain synaptic transmission and overcome short-term depression of synaptic transmission during repetitive firing. By enhancing plasma membrane tension, F-actin promotes fusion pore expansion, vesicular content release, and a fusion mode called shrink fusion involving fusing vesicle shrinking. Not only F-actin, but also the F-actin assembly pathway, including ATP hydrolysis, N-WASH, and formin, are involved in mediating these roles of exo- and endocytosis. Neurological disorders, including spinocerebellar ataxia 13 caused by Kv3.3 channel mutation, may involve impairment of F-actin and its assembly pathway, leading in turn to impairment of exo- and endocytosis at synapses that may contribute to neurological disorders.